Tkinter GUI application development hotshot : develop exciting and engaging GUI applications in Python and Tkinter by working on 10 real-world applications - Chaudhary, Bhaskar (Packt Publishing, 2013)
Practical, real-world example projects. Start with the topics that grab your attention or work through each project in sequence. If you have just started with GUI programming, this book is ideal for you. This book is also great if you are an experienced software developer, scientist, researcher, engineer, student, or hobbyist.